Chinese Indonesians reassessed: history, religion and belonging - Sai, Siew-Min; Hoon, Chang-Yau (Routledge contemporary Southeast Asia series, 2013)
"Shows how the Chinese minority is much more diverse, and the picture much richer and more complicated, than previous studies have allowed. Subjects covered include the historical development of Chinese communities in peripheral areas of Indonesia, the religious practices of Chinese Indonesians, which are by no means confined to "Chinese" religions, and Chinese ethnic events, where a wide range of Indonesians, not just Chinese, participate"--Provided by publisher